Love-Based Curriculum from the Perspective of Spritual and Character Education in Mandrasah 'Aliyah - Rohman; Rafiqa Noviyani; Rizqa Octarina; Kholidah Nur (Universitas Nahdatul Ulama Surabaya, 2026)
This study is grounded in concerns regarding the prevailing educational orientation that predominantly emphasizes academic and cognitive achievement, while frequently neglecting affective, spiritual, and moral dimensions. Such an imbalance has contributed to diminished levels of empathy and social awareness among students. Accordingly, a more holistic educational model is required—one that harmoniously integrates intellectual, emotional, and spiritual intelligence—conceptualized in this study as a love-based curriculum.. The purpose of this research is to examine the concept and implementation of a love-based curriculum from the perspective of spiritual and character education at Darussalam Simpang Limun Bangai Private Islamic Senior High School. The study employs a qualitative approach using a descriptive research design. Data were collected through classroom observations, in-depth interviews, and document analysis. The data analysis followed the Miles and Huberman interactive model, encompassing data reduction, data display, and conclusion drawing and verification. The validity of the findings was ensured through triangulation of both data sources and research methods. The findings indicate that the love-based curriculum is implemented through the integration of spiritual and character values into teaching and learning activities at the madrasah. Teachers play a pivotal role as moral exemplars, and their empathetic personal engagement significantly facilitates the internalization of love-based values among students. Nevertheless, several challenges remain, including limited professional training for teachers and insufficient collaboration between the madrasah and parents. The study recommends systematic educator training and the comprehensive integration of love-based values across curricular components to strengthen the implementation of this educational model.